Some Suggestions for Creating Nature Conservation Consciousness - Vaishnav, M. N. (Indian Forester, 1970)
Land, air and water resonrces which are indidpensable to life constitute social values. For greater prosperity and perpetual advantages, wise use of these energY resources is essential. Unless the public is made to understand the importance of conservation benefits, the phunder of this planet will go on endlessly. In the following paragraphs, the importance of nature conservation and suggestions to achieve the goal of creating conservation consciousness amongst the public have been discussed.